Implicações da vida humana na filosofia política de H. Arendt e G. Agamben - Cruz, Daniel Nery da (Universidade do Vale do Rio dos Sinos, 2018)
The problem discussed in this thesis is the centrality of life and its connection with politics in Agamben and Arendt thinking. Agamben realized that Hannah Arendt did not continue his research on politics, creating a gap, since she did not make the connection between life and the field, in other words, she did not establish a bond between zoé and the space of the sovereign exception. From this point of view, it is possible to investigate how much political philosophy of Agamben is influenced and finds conection in the political ideas of Hannah Arendt. Based on this, we analyze life as a purely biological problem and its political implications. It is considered that Agamben presents the concept of nude life not like Foucault’s formulations, who understands life in a unified vision, but seeking inspiration, as well as Arendt, in ancient Greek philosophy, that does not have a single definition of life, since life is presented as zoé (natural life), bios (political life) and bios theoretikos (contemplative life). Then, the theme of this project is the issue of life in Agamben's political thinking and his interpretation of Arendt's reflections, relating it to economic and political notions. During this analysis, we also verify the link between animal laborans, developed by the Arendtian theory, and homo sacer, in Agambenian thought. Besides, it is clarified how each author investigates and develops the concept of society and its nexus with the notion of oikonomia. From the analysis of these implications, the central hypothesis, in both authors, is that the possibility of a policy no longer linked to the devices of capture of life by oikonomia, but related to the potency of life as a philosophical category, in order to create an action that goes beyond predictability, based on autonomy (Arendt) and the potency of non (Agamben), building the horizon of politics which comes.
Keywords: Agamben; Arendt; Biopolítica; Vida; Agamben; Arendt; biopolitics; Life; ACCNPQ::Ciências Humanas::Filosofia